Alternative approaches for monitoring and evaluation of lymphatic filariasis following mass drug treatment with ivermectin, diethylcarbamazine and albendazole in East New Britain Province, Papua New Guinea. - Krufinta Bun; Benedict Mode; Melinda Susapu; Joyceline Salo; Catherine Bjerum; Michael Payne; Daniel Tisch; Makoto Sekihara; Emanuele Giorgi; Gary J Weil; Peter U Fischer; Leanne Robinson; et al. (PLoS Neglected Tropical Diseases)
Background WHO recommends two annual rounds of mass drug administration (MDA) with ivermectin, diethylcarbamazine, and albendazole (IDA) for lymphatic filariasis (LF) elimination in treatment naïve areas that are not co-endemic for onchocerciasis such as Papua New Guinea (PNG). Whether two rounds of MDA are necessary or sufficient and the optimal sampling strategies and endpoints for stopping MDA remain undefined. Methods and findings Two cross-sectional studies were conducted at baseline (N = 49 clusters or villages) and 12 months after mass drug administration (MDA) with IDA (N = 47 villages) to assess lymphatic filariasis (LF) by circulating filarial antigenemia (CFA) and microfilariae (Mf). Before MDA, children aged 6-9 years (N~50) and those  ≥  10 years (N~50) in each village were randomly sampled. Before MDA, the population mean prevalence of LF in East New Britain Province (ENBP), Papua New Guinea, was estimated using population proportionate sampling (PPS, N = 30) to be 59/2,561 (2.3%) CFA positive and 14/2,561 (0.6%) Mf positive. No children were Mf positive. However, LF infection was highly heterogeneous; 8 villages (26.7%) had a CFA prevalence >2%, and 7 villages (23.3%) had an Mf prevalence >1%. To identify sentinel villages with LF in areas under-sampled by PPS, 19 additional villages suspected to have LF were sampled, with 15 (79%) having >2% CFA prevalence and 7 (38%) >1% Mf (range 1-22%). Twenty-four villages were evaluated before and after MDA in age-matched adults ( ≥  18 years). Treatment reduced CFA prevalence by 34% and Mf prevalence by 90%. Post-MDA model-based geostatistics efficiently selected an additional 23 villages, of which 20 (87%) had a CFA prevalence  >  2%. None of these villages had >1% Mf. Post-MDA, two of four districts had no villages with >1% Mf. Conclusions Model-based geostatistics was more effective than PPS in sampling high-risk LF sites in a heterogeneous area. Low LF prevalence and partial reduction of CFA limit children's effectiveness as sentinels. A single round of high-coverage MDA with IDA achieved elimination targets in low-prevalence villages in PNG. Higher-prevalence areas will need additional MDA rounds, which could be targeted to smaller evaluation units to cut costs. Trial registration Clinicaltrials.gov NCT04124250.